FaGAPC2/FaPKc2.2 and FaPEPCK reveal differential citric acid metabolism regulation in late development of strawberry fruit - Yang, Min; Hou, GouYan; Peng, YuTing; Wang, LiangXin; Liu, XiaoYang; Jiang, YuYan; He, CaiXia; She, MuSha; Zhao, ManTong; Chen, Qing; Li, Mengyao; Zhang, Yong; et al. (Frontiers in Plant Science, 2023)
Abstract：Citric acid is the main organic acid in strawberry fruit, which is also an important factor affecting strawberry fruit quality and flavor. Its metabolic regulation is poor understood, but recently the key glycolytic genes, cytosolic glyceraldehyde-3-phosphate dehydrogenase (FxaC_14g13400, namely FaGAPC2) and pyruvate kinase (FxaC_15g00080, namely FaPKc2.2) were shown to be required for organic metabolism in strawberry fruits. In this study, we analyzed the pattern of citric acid accumulation during strawberry fruit development. The results showed that the citric acid content showed a trend of rising and then decreasing from partial red to full red then to dark red stage. A difference in citric acid metabolic regulation was suspected during strawberry fruit development. This idea was supported by further transient overexpression experiment. Both FaGAPC2 and FaPKc2.2 overexpression arrested strawberry fruit ripening, which was in a maturation state between partial red to full red, and the accumulation of citric acid was inhibited. The combined transcriptome and metabolome analysis revealed that FaGAPC2/FaPKc2.2 overexpression significantly suppressed the expression of phosphoenolpyruvate carboxykinase (FxaC_1g21491, namely FaPEPCK) and enhanced the content of glutamine and aspartic acid. Enzymatic assays demonstrated that FaGAPC2 and FaPKc2.2 overexpression inhibited PEPCK and glutamate decarboxylase (GAD) activities, but increased glutamine synthase (GS) activities. In addition, FaPEPCK overexpression promoted strawberry fruit ripening, which was in a maturation state between full red to dark red stage, and the citric acid synthase (CS) activities and citric acid content were significantly decreased. These results could imply that FaGAPC2 and FaPKc2.2 promote the degradation of citric acid mainly through inhibiting strawberry fruit ripening and enhancing GS pathway from partial red to full red stage, and FaPEPCK reduces citric acid content mainly through promoting strawberry fruit ripening and inhibiting citric acid synthesis from full red to dark red stage. This study provides new insights into the differential regulation citric acid metabolism underlying strawberry fruit development and ripening.